2010
DOI: 10.1007/s00253-010-2503-9
|View full text |Cite
|
Sign up to set email alerts
|

An improved transconjugation protocol for Bacillus megaterium facilitating a direct genetic knockout

Abstract: We provide a simple but very efficient transconjugation protocol for Bacillus megaterium. By combining utile attributes of known transconjugation methods (small size of the transferred DNA, close physical contact between donor and recipient cells, and heat treatment of the latter) and by determining the appropriate donor/recipient ratio, mating approaches yielded 5 x 10(-5) transconjugants/recipient. Counter-selection for eliminating Escherichia coli donor cells from the mating mixture was possible by pasteuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The latter, for instance, possesses 33 orthologs of genes involved in competence development in B. subtilis (Eppinger et al 2011), and functionality of the DNA receptor protein ComEA has been demonstrated in B. subtilis (Lammers et al 2004). However, B. megaterium was never reported to develop natural genetic competency, and that is why rather time-consuming, less efficient genetic methods such as the polyethylene-glycol-mediated protoplast procedure or transconjugation has to be applied to obtain transformants Meinhardt et al 1989;Richhardt et al 2010;Vary 1994;Vary et al 1982).…”
Section: Introductionmentioning
confidence: 96%
“…The latter, for instance, possesses 33 orthologs of genes involved in competence development in B. subtilis (Eppinger et al 2011), and functionality of the DNA receptor protein ComEA has been demonstrated in B. subtilis (Lammers et al 2004). However, B. megaterium was never reported to develop natural genetic competency, and that is why rather time-consuming, less efficient genetic methods such as the polyethylene-glycol-mediated protoplast procedure or transconjugation has to be applied to obtain transformants Meinhardt et al 1989;Richhardt et al 2010;Vary 1994;Vary et al 1982).…”
Section: Introductionmentioning
confidence: 96%
“…Thermo-alkaliphilic endo-1, 4-β-xylanases from Bacillus halodurans has been cloned and expressed in E. coli using pET21d with T7 promoter and the gene product showed the high potential in deinking of waste paper 8 To improve the gene expression stability and cut plasmid-maintenance, we firstly, cloned this gene with its original promoter then subcloned into pSKE194 vector, and integrated the gene into B. subtilis DB104 chromosome. In this study, we use pSKE194 plasmid constructed by Nahrstedt et al 9,10 which is a derivative plasmid from a combination between pE194 (plasmid for Bacillus) and pBluescript SK+ plasmid (for E. coli) 11 . Having combined features from its parental, this plasmid is a shuttle vector for both E. coli and B. subtilis which carries erythromycin (Erm) and ampicillin (Amp R ) resistance genes for recombinant selection.…”
Section: Introductionmentioning
confidence: 99%
“…It is also able to conduct spontaneous integration because of its thermo-sensitive origin of [DOI:10.24214/jcbps.B.9.3.131931.] replication which makes it fail to replicate at 42 o C and above 9,12 , allowing the target gene to integrate into chromosome without recE gene complex 7,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, genetic manipulation of B. megaterium is difficult, primarily because of low transformation efficiency. Richhardt et al [72] developed a simple and efficient transconjugation method for B. megaterium , combining a known transconjugation method [73] and B. subtilis sacB , which encodes levansucrase. The activity of this enzyme in the presence of sucrose is lethal to E. coli [74], so it is used as a counter-selection marker to eliminate the E. coli donor cells after mating.…”
Section: Introductionmentioning
confidence: 99%